2020
DOI: 10.1002/mrd.23417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotinamide supplementation in in vitro fertilization medium on bovine embryo development

Abstract: Increased oxidative stress is one of the main causes of poorly developed embryos in assisted reproductive technologies. Nicotinamide (NAM) has been shown to suppress reactive oxygen species (ROS) production through its potent antioxidative and anti-senescent effects. In the present study, we explored the effects of short-term NAM-treatment (3 and 5 h) during in vitro fertilization (IVF) on the development of bovine embryos. Treatment with 10 mM NAM for 3 h significantly increased the blastocyst formation but e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…El Sheikh et al suggested that during bovine oocyte IVM, 0.1 mM NAM supplementation enhanced cumulus cell expansion, increased the percentage of MII oocytes, significantly reduced ROS, and improved subsequent embryo development by activating the sirtuin1/threonine-specific protein kinase B (AKT) signaling pathway, although high concentrations (> 10 mM) of NAM had the opposite effect [ 46 ]. It was found that 10 mM NAM treatment in the IVF medium of bovine-fertilized embryos for 3 h reduced ROS in embryonic cells and significantly increased sirtuin1 expression and the blastocyst formation rate, indicating that NAM enhanced the developmental competence of bovine embryos in vitro via antioxidant activity [ 47 ]. However, a study showed that 20 mM NAM caused ROS accumulation and mitochondrial dysfunction in bovine oocytes, impairing oocyte maturation and embryonic developmental potential [ 48 ] Furthermore, in a review, investigators have pointed out that 5 mM NAM has a positive effect on the viability and replication of cells, but NAM exceeding 20 mM causes cell apoptosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…El Sheikh et al suggested that during bovine oocyte IVM, 0.1 mM NAM supplementation enhanced cumulus cell expansion, increased the percentage of MII oocytes, significantly reduced ROS, and improved subsequent embryo development by activating the sirtuin1/threonine-specific protein kinase B (AKT) signaling pathway, although high concentrations (> 10 mM) of NAM had the opposite effect [ 46 ]. It was found that 10 mM NAM treatment in the IVF medium of bovine-fertilized embryos for 3 h reduced ROS in embryonic cells and significantly increased sirtuin1 expression and the blastocyst formation rate, indicating that NAM enhanced the developmental competence of bovine embryos in vitro via antioxidant activity [ 47 ]. However, a study showed that 20 mM NAM caused ROS accumulation and mitochondrial dysfunction in bovine oocytes, impairing oocyte maturation and embryonic developmental potential [ 48 ] Furthermore, in a review, investigators have pointed out that 5 mM NAM has a positive effect on the viability and replication of cells, but NAM exceeding 20 mM causes cell apoptosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue culture buffer was provided by 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid [25]. Stem cell development was facilitated by Glutamax, nicotinamide, and human epidermal growth factor (EGF) [26][27][28]. Stem cells were maintained by B27 and human noggin [29,30], while N2 promoted their survival [31].…”
Section: The Medium Composition Of the Gim-ali Modelmentioning
confidence: 99%